Ultra-ductile and strong in-situ fibrillated PLA/PTFE nanocomposites with outstanding heat resistance derived by CO2 treatment. (April 2022) - Chai, Jialong; Wang, Guilong; Zhang, Aimin; Li, Shuai; Zhao, Jinchuan; Zhao, Guoqun; Park, Chul B.
Highlights: In-situ fibrillated PLA/PTFE nanocomposites were prepared. PTFE nanofibrils led to remarkably accelerated crystallization of PLA. CO2 treatment under room temperature can derive significant crystallization of PLA. Ductile, strong and heat-resistant PLA/PTFE nanocomposites were achieved. Abstract: Polylactic acid (PLA) is a green substitution of traditional petroleum-based polymers due to its bio-friendly natures. However, high brittleness and poor heat-resistance significantly limit the wide applications of PLA. Herein, a novel strategy by coupling in-situ fibrillation and CO2 treatment was developed to fabricate strong and ductile PLA/PTFE nanocomposites with outstanding heat resistance. Reticulated PTFE nanofibrils with diameters of 100–200 nm were created in an in-situ way, which dispersed uniformly in PLA matrix. By further CO2 treatment under room temperature, those PTFE nanofibrils can derive many nanoscale transcrystals due to heterogenous nucleation effect. These nanocrystals together with PTFE nanofibrils led to dramatically enhanced ductility, strength, and heat resistance of PLA. Compared with pure PLA, the PLA/PTFE nanocomposite's ductility, strength, and Vicat softening temperature after CO2 treatment were increased by 270%, 17%, and 130%, respectively. Thus, this advanced methodology provides a promising way for developing high-performance environmentally friendly biocomposites.